2010
DOI: 10.1111/j.1440-1681.2010.05411.x
|View full text |Cite
|
Sign up to set email alerts
|

Orexin‐A and respiration in a rat model of smoke‐induced chronic obstructive pulmonary disease

Abstract: SUMMARY1. Orexins are neuropeptides synthesized in the hypothalamus that regulate many physiological functions, including energy homeostasis, stress responses, sleep ⁄ wake states etc. It is now emerging that orexins may also regulate breathing, but little is known as to how they do this, particularly in chronic obstructive pulmonary disease (COPD). In the present study, we used a rat model of cigarette smoke-induced COPD to investigate orexin-A expression in the hypothalamus and medulla and its effect on resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In a human study, orexin A plasma levels were dramatically increased in patients with chronic obstructive pulmonary disease (COPD), a condition associated with hypercapnia and a tenfold increased risk of panic attacks [66]. Consistent with this, chronic exposure to cigarette smoke tripled hypothalamic orexin A expression in a rodent model of COPD [67]. In addition, rat exposure to hypercapnic air increased c-Fos expression in orexin neurons, and promoted anxietylike behavior, which was prevented by systemic injection of SB334867 [68].…”
Section: Reviewmentioning
confidence: 84%
“…In a human study, orexin A plasma levels were dramatically increased in patients with chronic obstructive pulmonary disease (COPD), a condition associated with hypercapnia and a tenfold increased risk of panic attacks [66]. Consistent with this, chronic exposure to cigarette smoke tripled hypothalamic orexin A expression in a rodent model of COPD [67]. In addition, rat exposure to hypercapnic air increased c-Fos expression in orexin neurons, and promoted anxietylike behavior, which was prevented by systemic injection of SB334867 [68].…”
Section: Reviewmentioning
confidence: 84%
“…Ghrelin is also an important polypeptide that stimulates food intake (12,13). Orexins play an important role in various physiological events, including the stress response and the sleep/wake cycle (14). In a previous study, orexin-A levels in patients with COPD were reported to be lower than those in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not safe because of significant respiratory depression and other peripheral side effects. Recently, COPD was modeled in rats by exposing them to chronic cigarette smoke (1 h, twice/day over 12 weeks) (Liu et al, 2010). By week 12, the COPD rats compared with control rats, had: (1) COPD-associated lung pathology (ie, coalesced alveoli and thickened bronchiolar walls); (2) 4100% increase in hypothalamic and medullary ORX-A protein expression; and (3) heightened phrenic nerve responses to ORX-A injections into the pre-Bötzinger complex.…”
Section: Conclusion and Clinical Considerationsmentioning
confidence: 99%
“…Compared with ORX-B, ORX-A binds with a higher affinity to the ORX1 receptor, which is the receptor targeted here (for review, see Sakurai, 2007). This ORX system is critical for maintaining wakefulness (for review, see Sakurai, 2007) and a hyperactive ORX system is linked to: a rodent model of COPD (Liu et al, 2010); clinical COPD with hypercapnic respiratory disorder (Zhu et al, 2011); and anxiety-and panic-vulnerability in rats and humans (Johnson et al, 2010). Furthermore, during wakefulness prepro-ORX knockout mice have blunted respiratory responses to 5-10% hypercarbic gas exposure, and injecting wild-type mice with an ORX1 receptor antagonist attenuates hypercapnic-induced respiratory responses (Deng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%